Signal Processing, Sensor Fusion, and Target Recognition XV 2006
DOI: 10.1117/12.667793
|View full text |Cite
|
Sign up to set email alerts
|

Observable operator model-based joint target tracking and classification

Abstract: In this paper, a new joint target tracking and classification technique based on Observable Operator Models (OOM) is considered. The OOM approach, which has been proposed as a better alternative to the Hidden Markov Model (HMM), is used to model the stochastic process of target classification. These OOMs afford both mathematical simplicity and algorithmic efficiency compared to HMM. Conventional classification techniques use only the feature information from target signatures. The proposed OOM based classifica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…The detailed description of this algorithm is illustrated in Section 3. The OOM based target orientation estimator first classifies the target class (when more than one possible target class exists) using the feature measurement [22] and then process the feature measurements to model the target orientation density. The estimated target orientation is used as a measurement for target tracking.…”
Section: Figure 2 Tracking Diagrammentioning
confidence: 99%
See 2 more Smart Citations
“…The detailed description of this algorithm is illustrated in Section 3. The OOM based target orientation estimator first classifies the target class (when more than one possible target class exists) using the feature measurement [22] and then process the feature measurements to model the target orientation density. The estimated target orientation is used as a measurement for target tracking.…”
Section: Figure 2 Tracking Diagrammentioning
confidence: 99%
“…The joint processing of the OOM orientation estimator and the target tracker improves both target tracking as well as the orientation measurement estimation. It has been shown that joint processing of information improves effective performance of the algorithms than treating them separately [6] [7] [22]. The feature/amplitude information from each sensor has measurement origin uncertainties due to clutter and multitarget environment.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation